Identification and Analysis of NBS-LRR Genes in Actinidia chinensis Genome - Tao Wang; Zhan-Hui Jia; Ji-Yu Zhang; Min Liu; Zhong-Ren Guo; Gang Wang (Plants, 2020)
Nucleotide-binding site and leucine-rich repeat (NBS-LRR) genes represent the most important disease resistance genes in plants. The genome sequence of kiwifruit (Actinidia chinensis) provides resources for the characterization of NBS-LRR genes and identification of new R-genes in kiwifruit. In the present study, we identified 100 NBS-LRR genes in the kiwifruit genome and they were grouped into six distinct classes based on their domain architecture. Of the 100 genes, 79 are truncated non-regular NBS-LRR genes. Except for 37 NBS-LRR genes with no location information, the remaining 63 genes are distributed unevenly across 18 kiwifruit chromosomes and 38.01% of them are present in clusters. Seventeen families of cis-acting elements were identified in the promoters of the NBS-LRR genes, including AP2, NAC, ERF and MYB. Pseudomonas syringae pv. actinidiae (pathogen of the kiwifruit bacterial canker) infection induced differential expressions of 16 detected NBS-LRR genes and three of them are involved in plant immunity responses. Our study provides insight of the NBS-LRR genes in kiwifruit and a resource for the identification of new R-genes in the fruit.